2019
DOI: 10.1111/myc.12997
|View full text |Cite
|
Sign up to set email alerts
|

Combination of β‐(1, 3)‐D‐glucan testing in serum and qPCR in nasopharyngeal aspirate for facilitated diagnosis of Pneumocystis jirovecii pneumonia

Abstract: Summary Background Currently, the biological diagnosis of Pneumocystis jirovecii pneumonia (PjP infection) usually relies on microbiological investigations in bronchial‐alveolar lavage fluid (BALF) by conventional staining methods and/or molecular biology. However, bronchial‐alveolar lavage is sometimes complicated to manage, especially in weakened patients. Therefore, alternative clinical samples—easier to collect—are warranted in such specific contexts. Objective Over a four‐year period, diagnostic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Nasopharyngeal aspirate and oral wash PCR sensitivities were both numerically lower than induced sputum PCR, at 89% and 77% (compared to 99%), respectively, but had similar J o u r n a l P r e -p r o o f specificities. It is important to recognize that studies reporting on nasopharyngeal aspirates [35,56] consisted of true aspirates (as opposed to swabs); thus, the diagnostic accuracy of nasal swab PCR still requires separate investigation. Oral wash PCR performed similarly to what has been described previously in a smaller meta-analysis of 4 studies [77] when compared with our studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasopharyngeal aspirate and oral wash PCR sensitivities were both numerically lower than induced sputum PCR, at 89% and 77% (compared to 99%), respectively, but had similar J o u r n a l P r e -p r o o f specificities. It is important to recognize that studies reporting on nasopharyngeal aspirates [35,56] consisted of true aspirates (as opposed to swabs); thus, the diagnostic accuracy of nasal swab PCR still requires separate investigation. Oral wash PCR performed similarly to what has been described previously in a smaller meta-analysis of 4 studies [77] when compared with our studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that quantitative PCR (qPCR) or realtime PCR (RT-PCR) could be used to discern active infection from colonization, although this has yet to be proven [79]. Owing to the lower fungal burden in minimally invasive samples compared to BAL [35], one could hypothesize that the risk of false positive might be lower using a minimally invasive specimen compared to BAL, but this needs to be specifically investigated. This could explain why the specificities for non-invasive PCR appeared to be higher (94-98%) than those reported for BAL PCR (91%) [9], as has been described previously [78].…”
Section: Discussionmentioning
confidence: 99%
“…The overall specificity of 79% is lower that the subgroup-specific specificity for HIV (83%; 95%CI 69e92%) and non-HIV (83%; 95%CI 72e90%). This is because there are five studies [22,25,33,36,42] included in the overall estimates that include HIV-positive patients but do not provide stratified data.…”
Section: Discussionmentioning
confidence: 99%
“…26 It was recently shown that serum (1→3)-β-D-glucan levels of 143 pg/mL can be used to distinguish PCP from colonisation with P. jirovecii. 28 To diagnose and treat PCP you have to have a lot of experience. 29 Our results were not concordant with latter studies because we measured much higher (1→3)-β-D-glucan levels in the patients with true PCP.…”
Section: Discussionmentioning
confidence: 99%